Elevating glucose and insulin secretion by carbohydrate formulation diets in late lactation to improve post‐weaning fertility in primiparous sows. (23rd August 2016) - Chen, TY; Lines, D; Dickson, C; Go, C; Kirkwood, RN; Langendijk, P
Contents: Primiparous (P1) sows commonly lose excessive body reserves to meet energy requirements for maintenance and milk production during lactation, and consequently, post‐weaning reproductive performance may be compromised. The present studies determined whether ad libitum feeding a glucogenic carbohydrate diet (CHO) during late lactation could stimulate insulin and glucose secretion (experiment 1) and improve subsequent litter size (experiment 2). For experiment 1, 15 P1 sows, and for experiment 2, 99 P1 sows (198.5 ± 2.7 kg) were allocated randomly according to suckled litter size (≥10 piglets), either to a CHO diet (14.3 MJ DE/kg, 19.8% crude protein) or a standard lactation diet (control; 14.2 DE MJ/kg, 19.5% crude protein) at 8 days before weaning. The CHO diet aimed to provide glucogenic content (extruded wheat, dextrose and sugar) as energy sources instead of fat sources without changing total dietary energy. Pre‐prandial plasma glucose and insulin concentrations were not influenced by treatments. However, post‐prandial plasma glucose and insulin concentrations and their peaks were both higher ( p  < .05) compared to the control treatment. Body weight loss during lactation was relatively low at 3%–4% for both treatments and did not differ between control and CHO treatments (−7.6 ± 1.6 vs −5.4 ± 1.2 kg; p  > .05). Second litter size was not influenced by diet ( p  > .05), but the weaning‐to‐mating interval was shorter in CHO sows ( p  < .05). This study demonstrates that providing an enriched CHO diet in late lactation did influence post‐weaning follicle growth but did not improve subsequent litter size. This may be due to the primiparous sows in this study not experiencing severe negative energy balance and there was no second litter syndrome in this farm which limited the ability of diet to improve sow fertility.